2020
DOI: 10.1007/s11517-020-02228-3
|View full text |Cite
|
Sign up to set email alerts
|

Visco-hyperelastic characterization of human brain white matter micro-level constituents in different strain rates

Abstract: In this study, we propose a computational characterization technique for obtaining the material properties of axons and extracellular matrix (ECM) in human brain white matter. To account for the dynamic behavior of the brain tissue, data from timedependent relaxation tests of human brain white matter in different strain rates are extracted and formulated by a viscohyperelastic constitutive model consisting of the Ogden hyperelastic model and the Prony series expansion. Through micromechanical finite element si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Recent efforts towards micromechanical modeling of brain tissue have proposed to include the individual contributions of axons and extracellular matrix in white matter tissue [25,42] or the brain stem [2,26] through representative volume elements accounting for the distribution and orientation of nerve fiber bundles from magnetic resonance and diffusion tensor imaging data. However, it remains controversial whether axons indeed majorly contribute to the mechanical response of brain tissue [12,15,20,51] and such models would only be valid for certain white matter areas.…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts towards micromechanical modeling of brain tissue have proposed to include the individual contributions of axons and extracellular matrix in white matter tissue [25,42] or the brain stem [2,26] through representative volume elements accounting for the distribution and orientation of nerve fiber bundles from magnetic resonance and diffusion tensor imaging data. However, it remains controversial whether axons indeed majorly contribute to the mechanical response of brain tissue [12,15,20,51] and such models would only be valid for certain white matter areas.…”
Section: Introductionmentioning
confidence: 99%
“…While the meninges could be possibly modeled as a viscous fluid with the material properties of water ( Singh et al, 2014 ), we do not expect such properties to significantly modify the simulated pressure-time profiles because other studies that approximated the meninges using the Mie-Gruneisen equation of state for water observed oscillations in the model-predicted ICP for blast-loading conditions ( Garimella et al, 2018 ; Tong et al, 2019 ). Finally, we assumed homogeneous properties for the brain tissue and necessarily excluded rate-dependent material properties specific to brain white matter ( Tse et al, 2017 ; Ramzanpour et al, 2020 ), which could possibly influence VMS and MPS values. Nonetheless, as the redistribution of MPS resulting from the inclusion of vasculature is consistent for homogeneous and heterogeneous brain-tissue properties ( Zhao and Ji, 2020 ; Subramaniam et al, 2021 ), we expect our overall findings to remain valid.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Rohner et al [193], reported 14.1% generation of new bone in a pig model after three months, using PCL scaffolds prepared by FDM and coated with bone marrow. Several clinical studies have also shown that PCL scaffolds manufactured by FDM have favorable biocompatibility and a low cost of manufacturing, leading to approval by the US Food and Drug Administration for use in human bone tissue [194][195][196][197]. Currently commercialized products manufactured by FDM include Osteoplug™ and Osteomesh™ (Osteopore), which are thin interwoven meshes and three-dimensional implants respectively as it can be seen in Figure 9.…”
Section: Fused Deposition Modeling (Fdm)mentioning
confidence: 99%